Implementasi Strategi Manajemen Pemasaran Bank Syariah di Era Revolusi Industri 4.0 di Indonesia - Nabila Arifa Aprilia Putri David; Muhammad Iqbal Fasa; Suharto Suharto (LABATILA: Jurnal Ilmu Ekonomi Islam, 2022)
Marketing strategy is a planned and structured marketing procedure that will be carried out to achieve company goals. Along with the development of a company, the company's competition is unavoidable, especially in the banking world. The formulation of the problem in this study is how the strategy for marketing Islamic banking is to continue to advance and exist in this era of the fourth industrial revolution. This study aims to find out how the implementation of Islamic bank marketing management strategies in the era of the industrial revolution 4.0 in Indonesia today. This research is a qualitative research through the collection of detailed and in-depth data by involving various sources of information. The results of the research that can be obtained are the development of marketing strategies for Islamic banking, namely optimizing products that encourage optimization of business profits, improving the quality of human resources, increasing technological sophistication and increasing product quality. The development of Islamic bank marketing strategies with SWOT analysis, namely: 1) Strengths-Opportunities Strategy, 2) Weaknesses-Opportunities Strategy, 3) Strengths-Threats Strategy, 4) Weaknesses-Threats Strategy.